If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 + 3x + -2x = 17 Combine like terms: 3x + -2x = 1x -7 + 1x = 17 Solving -7 + 1x = 17 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 1x = 17 + 7 Combine like terms: -7 + 7 = 0 0 + 1x = 17 + 7 1x = 17 + 7 Combine like terms: 17 + 7 = 24 1x = 24 Divide each side by '1'. x = 24 Simplifying x = 24
| 5y^5=20 | | 3500+1680x=175000+550x | | 8(3n-8)=8 | | 5.9-p=2 | | x-153=55+9x | | 6.3=7.0x | | -4.5(7x-6.5)=-23.5 | | 52-4x=10-10x | | 3x-2(x-3)+4(x+1)=-5 | | 2x-102-10x=42 | | -9(5-5.5k)=26.5 | | 14-8m= | | -77-10x=165+x | | 5ab*3= | | 5r-14=-44 | | 10x-1=6x+10 | | =9xy^2+6xy-5x | | 24+8y-16w= | | 2(7x-13)=16 | | 5x+(x+2)-3(x-4)=35 | | 5x+3+3x=83 | | 2(7x+13)=16 | | 2x-5+12=7(x-2) | | 3x-7=5+6x | | -2d-9.5d=-2.15 | | 8x+28=60 | | -3(-3r-6)=63 | | 8.5x=6y-c | | 6x-12=20x | | x-4(x+1)-2(x+3)=-60 | | 2(3x-6)=20x | | 8.5c+2.5-8c=22.5 |